The Implementation of Verdict Execution on Providing Maḍiyah Maintenance Following Divorce According to Islamic Law (Case Study in Syar’iyyah Court Banda Aceh) - Devy, Soraya; Suci, Dwi Mekar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
The article discusses the procedures of filing a plea to execute verdicts on providing māḍiyah maintenance and the effort to implement the verdicts in Syar’iyyah Court Banda Aceh. The study was conducted with a qualitative approach and the collected data were analyzed with a descriptive-analysis method based on Islamic law perspective. The result shows that the procedure and the legal effort to file an execution toward the verdict related to māḍiyah maintenance in Syar’iyyah Court are distinguished into two types of divorce, i.e. talak divorce and filed divorce. In talak divorce, the execution of the verdict related to maintenance is conducted during the reading of the talak pledge. In the filed divorce, the ex-wife’s lawsuit related to maintenance which is neglected by the ex-husband is entitled to be legally sued through filing a plea on execution. The phases as follows: (1) the ex-wife files a plea of execution to the court, (2) pay the execution cost, (3) aanmaning (a warning to the defendant), (4) the ex-husband and ex-wife comply with the summons by the court, (5) the court establishes executorial beslag (executing confiscation), (6) the court establishes an execution order, (7) an auction. According to the Islamic perspective, the execution of māḍiyah maintenance can be conducted following the ex-wife’s lawsuit to the court. The execution of māḍiyah maintenance can be performed by the court based on the valid provisions of executing māḍiyah maintenance in Syar’iyah Court upon consideration of benefit and expediency principles.